ḤIKMAH DALAM PERSFEKTIF ALQURAN - Muhyiddin Tahir (Hunafa: Jurnal Studia Islamika, 2012)
Abstract: The Qur’an is admitted by Muslims as a collection of God's words which have been recorded in the form of a book. The word ḥikmah is one of the words repeatedly stated in the Qur’an, but the word will have its own meaning, when coupled with specific words in the Qur’an. Therefore, the use of the word in the Qur'an should be interpreted and understood. That understanding can be extracted from the Qur'an itself, which is also considered the ḥikmah because it is full of wisdom that should be applied, both in individual life and in the social life.Kata Kunci: hikmah, Alquran, mawā’iẓ, kenabian